North Korean migrants in China: whether illegal migrants, refugees, or human trafficking victims - Bak, Hyeong a (Lexington Books, 2024)
"Hyoungah Park interviews fifty-eight North Korean migrants in China and analyzes their stories, exploring why they decided to escape North Korea despite the risks, how they escaped, and their experiences being victimized by human trafficking"--